Nacionalismo e música erudita de vanguarda no Brasil e Argentina: Camargo Guarnieri e Alberto Ginastera (1930-1960) - Ornaghi, Mário André [UNESP] (2013)
From the artistic careers of composers Alberto Ginastera and Camargo Guarnieri, this essay aims to analyze the consequences of nationalism and musical ―avant-garde‖ in Argentina and Brazil from 1930 to 1960. So, we will develop a focus compared between these two countries in a way that these trajectories can be analyzed in line with broader intellectual paradigms – including international ones - that ended up favoring certain aesthetic forms in different periods covered. We believe that the artistic options of Ginastera and Guarnieri are related to the musical past of their respective societies, hence the importance of discussing the Argentine and Brazilian cultural history, as well as the place and the strength that the nationalist movements and ―avantgarde‖ aesthetics forms found there